2021
DOI: 10.1080/10872981.2021.1875531
|View full text |Cite
|
Sign up to set email alerts
|

Effect of absenteeism on the performance of medical sciences students: gender differences

Abstract: The effects of the learning environment on academic performance can be investigated according to a broad range of factors using a diversity of approaches. Many differences in academic performance have been associated with the sex of the student. Objectives : This study aims to understand the impact of absenteeism on the final grades earned by full-time medical laboratory sciences undergraduate students and whether this is affected by sex. Academic performance was analyzed using students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 35 publications
1
10
0
1
Order By: Relevance
“…Finally, we also look at the role student gender plays on absenteeism and their CGPA (Cummulative GPA). As shown in the study by Hakami (2021), gender was considered a confounding variable and he found that absenteeism is a negative predictor for males but not females studying medical sciences. These results were corroborated by Valli Jayanthi et al (2014) who measured academic performance using CGPA and showed that student grades are affected by gender, extracurricular activities, and age.…”
Section: Literature Reviewmentioning
confidence: 96%
See 1 more Smart Citation
“…Finally, we also look at the role student gender plays on absenteeism and their CGPA (Cummulative GPA). As shown in the study by Hakami (2021), gender was considered a confounding variable and he found that absenteeism is a negative predictor for males but not females studying medical sciences. These results were corroborated by Valli Jayanthi et al (2014) who measured academic performance using CGPA and showed that student grades are affected by gender, extracurricular activities, and age.…”
Section: Literature Reviewmentioning
confidence: 96%
“…The term absenteeism has been defined as the conscious and deliberate act of being away from the physical space of the University classroom, conditioned on some factors that influence the search for alternatives to the use of time (Crespo et al, 2012). Within education assessment, absenteeism is a key variable that can affect students' academic performance (Hakami, 2021). During middle of the spring semester in 2020, when most countries went into lock down, most universities distinguished and continue to distinguish between regular online classes (which formats predated the lock down; mostly asynchronous) and remote classes (which aimed to be as in-person like as possible; mostly synchronous) for the purpose of students' academic life from the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Cortright et al (2011) found that the influence of regular attendance on examination performance is more important for female students than for male students. Recently, Hakami (2021) found that the mean scores of female medical science students were significantly higher than those of male students for two academic semesters. Contrary to Cortright et al (2011) Hakami (2021 argues that absenteeism is a negative predictor of academic success for male medical science students, but not for female students.…”
Section: Conceptual Framework and Hypotheses Developmentmentioning
confidence: 99%
“…Recently, Hakami (2021) found that the mean scores of female medical science students were significantly higher than those of male students for two academic semesters. Contrary to Cortright et al (2011) Hakami (2021 argues that absenteeism is a negative predictor of academic success for male medical science students, but not for female students.…”
Section: Conceptual Framework and Hypotheses Developmentmentioning
confidence: 99%
“…A substantial body of evidence showed that the effect of the learning environment on academic performance can be investigated according to a broad range of factors, and many differences in academic performance have been associated with the gender of students [15], Burns and Bracey ( [16]; see also, [17]) viewed that male students' performance and grades have gaps from female students in academic achievement at their age of sixteen. That is to say, gender is an explicit factor that has an impact on students' present performance (e.g., mathematics; [18]), classroom interactions [19], and future achievements (e.g., self-efficacy; [20]).…”
Section: Introduction Of Research Backgroundsmentioning
confidence: 99%